Executive Committee Minutes 2011-02-17 - Academic Senate:::::::::
Agenda – approved. Approval of minutes of 2/3/11 – amended and approved. Chair's Report. President Report. Provost Report. FSAC Report. Course Repeat Policy revision approved for Senate agenda. Vice President of Administration and Finance Report. New Statistics minor and Revision to the Mathematics minor approved for Senate consent calendar. Engineering Science name change approved for Senate consent calendar. Vice President of SAEM Report. Revision to the Anthropology minor. APC Report. EPC Report. SAC Report. Associated Students Report. Senate Agenda approved. Good of the Order.